2015
DOI: 10.2174/1573402111666150401105317
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs and Hypertension–Unveiling Unexpected Mechanisms of Hypertension by the Dark Matter of the Genome

Abstract: Hypertension is a major risk factor of cardiovascular diseases and a most important health problem in developed countries. Investigations on pathophysiology of hypertension have been based on gene products from coding region that occupies only about 1% of total genome region. On the other hand, non-coding region that occupies almost 99% of human genome has been regarded as “junk” for a long time and went unnoticed until these days. But recently, it turned out that non-coding region is extensively transcribed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 134 publications
(109 reference statements)
0
15
0
Order By: Relevance
“…In recent years, with the development of sequencing technology, numerous genes and gene families have been identified. In addition, some transcriptomes, which were previously regarded as being "dark" or "junk" having either no or only a weak protein-coding ability, also have been identified [1][2][3]. However, multiple functions have recently been discovered for noncoding regions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the development of sequencing technology, numerous genes and gene families have been identified. In addition, some transcriptomes, which were previously regarded as being "dark" or "junk" having either no or only a weak protein-coding ability, also have been identified [1][2][3]. However, multiple functions have recently been discovered for noncoding regions.…”
Section: Introductionmentioning
confidence: 99%
“…Rather than just being affected by variations in the coding genome, epigenetic mechanisms, including microRNAs, histone modification, and methylation, are increasingly seen to play a role in the development of hypertension [101]. Non-coding areas of the human genome, which make up almost 99% of it, were long regarded as "junk DNA" [102]. In contrast, the Encyclopedia of DNA Elements (ENCODE) project has shown that non-coding DNA is a critical element of gene function regulation across cell, tissue, and organ types [103,104].…”
Section: Epigenomicsmentioning
confidence: 99%
“…Regulatory elements, such as transcription-factorbinding sites, histone modification, chromatin structure, and DNA methylation, are highly cell-type specific. Those non-coding regions are extensively transcribed into non-coding RNAs, such as microRNAs and long-non-coding RNAs (lncRNA), with various functions including the influence of the pathophysiology of hypertension [102]. For example, micro-RNAs seem to be associated with hypertension via sympathetic nerve activity, ion transporters in the kidney, endothelial function, vascular smooth muscle phenotype transformation, and communication between cells [102].…”
Section: Epigenomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…ncRNA is a functional RNA molecule that is transcribed from DNA, but not translated into proteins and has been shown to be involved in regulating gene expression and inhibiting the translation and degradation of messenger RNAs [ 13 ]. Two major types of ncRNA, namely microRNAs (miRNAs) and long non-coding RNAs (lncRNAs), have been extensively studied in both hypertensive patients and animal models as outlined in a number of review papers [ 14 , 15 ]. This review will present an update of the most recent progress in both miRNAs and lncRNA focusing on their links to the physiological regulation and therapeutic potential in systemic hypertension.…”
Section: Introductionmentioning
confidence: 99%